The analyses of Turkish apparel industry by the five forces model - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2013)
The analyses of Turkish apparel industry by the five forces The purpose of this article is to analyze Turkish apparel industry by using Porter's Five Forces Model. A survey has been developed through the sources in literature to gather data for this purpose. Survey applied to the 35 apparel companies from the Top and Next Top 500 Industrial Enterprises ranking conducted by Istanbul Chamber of Industry each year. And the results were evaluated by using frequency tables, Likert scale of comparisons. According to the findings obtained from the analyses, that competition between the existing companies in Turkish apparel industry was dense, due to the many similar sized companies, low exit barriers. In addition to this, threat of substitute products and bargaining power of the suppliers are not very high. Bargaining power of buyers is increasing because of global economic situation. Depending on the literature and the findings, a number of strategies were recommended to Turkish apparel industry to adopt for the competition.
Keywords: apparel industry; competitive advantage; Michael Porter's model